Effect of EGF on expression and localization of maturation-promoting factor, mitogen-activated protein kinase, p34 cdc2 and cyclin B during different culture periods on in vitro maturation of canine oocytes - Pereira, Leda Maria C. [UNESP]; Bersano, Paulo Ricardo O.; Rocha, Danilo D.; Lopes, Maria Denise [UNESP] (Wiley, 2019)
This study aimed to investigate the localization of MPF, MAPK, p34 cdc2 and cyclin B1 proteins, before and after treatment with EGF during different moments of oocyte maturation. The ovaries obtained from 350 domestic dogs were aseptically isolated, immersed in physiological solution and transported at 4°C. In the laboratory, the ovaries were sectioned for the release of cumulus–oocyte complexes. Cumulus–oocyte complexes were selected and divided into treatment groups with and without EGF and cultured for 24, 48 and 72 hr. Immunofluorescence was used for the detection and the localization of MAPK, MPF, p34 cdc2 and cyclin B1 proteins. We observed that the expression and localization of MPF, MAPK, p34 cdc2 and cyclin B1 proteins are associated with meiosis resumption and cell cycle progression, and that EGF influences cell signalling pathways by promoting alterations in the localization of these proteins, improving the acquisition of oocyte competence. This is the first report of the localization of crucial proteins for meiosis progression in domestic dogs and identification of the expression and localization of proteins for cell cycle progression performed in this study represented a step of great importance to elucidate the mechanisms involved in the meiosis block in domestic dogs, allowing the advance in this research area.